PENGARUH PENERAPAN PEMBELAJARAN BERBASIS MASALAH TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA NEGERI 3 REMBANG (Faculty of Social Science, Universitas Negeri Semarang, 2014)
he aims of this research method used is quasi-experiment with a 2x2 factorial design. Research population is 272 of teen grade students of SMA Negeri 3 Rembang in 2013/2014 academic year; he research sample taken is 152 student, which is detailed into 76 students for experiment class. Samples were taken by random sampling technique. The data collection techniques used are documentation and test. The techniques of data analysis used, is two way varian analysis (ANAVA) at significance level = 0.05. The analysis shows that : (1) There is differences between the use of problem based instruction and lecturing method on the student's achievement at economy subject of the teen grade students of SMA Negeri 3 Rembang in 2013/2014 academic year, the result can be shown FcountFtable or 41.7073.84 at significant level 5% with db=1. (2) There is differences between students students who have high critical thinking and low critical thinking on the student's achievement at economy subject of the teen grade students of SMA Negeri 3 Rembang in 2013/2014 academic year the tested truth can be shown FcountFtable or 18.1173.84 at significant level 5% with db=1. (3) There is influence interaction on the use of problem based instruction on the student's achievement at economy subject of the teen grade students of SMA Negeri 3 Rembang in 2013/2014 academic year, the tested truth can be shown FcountFtable or 9.500 3.84 at significant level db=1. The result of the scheffe test shows a various average among the students who have a high critical thinking get a higher learning achievement than students who have a low critical thinking.